Bargaining: Revisi Teori Perimbangan Kekuatan dalam Hubungan Diplomasi Indonesia, Malaysia, Cina dan Amerika Serikat - Ian Montratama; Yanyan Mochamad Yani (Departemen Hubungan Internasional, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Padjadjaran, 2017)
This article is aim to critisize the theory of balance of power and offer alternative strategy. For more than three centuries, Balance of Power (BOP) theory has served as the core of Realist. However, for lesser state that were facing stronger rivaling alliance power, BOP theory only serves two strategy options: Balancing and Bandwagoning. Both solutions are not fit for neutral lesser states, which should raise the needs for a newly engineered third strategy – that can increase relative power of lesser state, but keep its political neutrality. The third strategy is named Bargaining by Authors – that relies on strategic partnerships as diplomatic instrument.